Determinants of financial performance in Malaysia: evidence from commercial banks / Zuhri Irfan Azrai and Siti Mastura Mohd Yusoff - Azrai, Zuhri Irfan; Mohd Yusoff, Siti Mastura (Faculty of Business and Management, 2019)
This study is carried out to examine the determinants of financial performance in Malaysia evidence from commercial banks. There are five bank-specific determinants selected namely credit risk, liquidity risk, bank size, capital adequacy and management efficiency. Six local commercial banks have been chosen to represent the commercial banks in Malaysia which are Malayan Banking Berhad (Maybank), CIMB Bank Berhad, Public Bank Berhad, RHB Bank Berhad, Hong Leong Bank Berhad and AmBank Group Berhad. The duration for this study is from 2004 until 2017 and the data is extract from annual report of commercial banks. Panel Regression Fixed Effect Model are carried out to investigate the finding from data. In the findings, two independent variables which are liquidity risk (LR) and management efficiency (ME) shown that they are statistically significant to the return on assets (ROA). However, the other independent variables which are credit risk (CR), bank size (BS) and capital adequacy (CA) are insignificant towards ROA of financial performance in Malaysia.